2022
DOI: 10.3390/app12052359
|View full text |Cite
|
Sign up to set email alerts
|

Are the Currently Available Elastography Methods Useful in the Assessment of Chronic Kidney Disease? A Systematic Review and a Meta-Analysis

Abstract: Background: We require an quantitative imaging technique for the diagnosis and assessment of chronic kidney disease (CKD). Renal elastography has been widely used in recent years in different studies; however, the results across them are not consistent and, as a result, we conducted a meta-analysis of the published literature on this topic. Methods: The databases of PubMed, Medscape, Medline were searched for all studies published in English from 2010 until November 2021 that evaluated kidney shear wave speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…A recent meta-analysis of renal elastography investigations demonstrated that patients with a lower eGFR had lower kidney stiffness on average. However, even though renal elastography appears to be a promising method for monitoring CKD progression, studies up to date reveal great heterogeneity [ 32 ]. As intrarenal blood flow decreases as fibrosis progresses, alterations in renal perfusion may influence renal stiffness and explain some inconsistencies in results.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of renal elastography investigations demonstrated that patients with a lower eGFR had lower kidney stiffness on average. However, even though renal elastography appears to be a promising method for monitoring CKD progression, studies up to date reveal great heterogeneity [ 32 ]. As intrarenal blood flow decreases as fibrosis progresses, alterations in renal perfusion may influence renal stiffness and explain some inconsistencies in results.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in renal stiffness with the progression of CKD has also been shown in other kidney elastography studies [ 10 , 13 , 28 , 29 , 30 , 31 , 32 , 33 ], but there have also been some studies that revealed an increase in stiffness as the disease progressed [ 11 , 34 , 35 , 36 , 37 ]. Despite the fact that renal elastography seems to be a viable technique for tracking the progression of CKD, existing research has revealed substantial differences among such techniques [ 38 ]. The high degree of anisotropy of the kidney [ 39 ] or modifications in renal blood flow may have an impact on renal stiffness and justify the discrepancies in the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus more comprehensive studies on DMSA scans should be conducted in the future, especially including follow-up scintigraphy, to provide further details on this topic. Another recent meta-analysis study on patients with CRF reported that renal SWV was generally lower in different elastography studies and that the results of various studies differed significantly [16]. Similar to a previous meta-analysis [4], it was suggested that renal elastography could not be considered a solid element of routine monitoring because it required technical improvements.…”
Section: Discussionmentioning
confidence: 79%